The development of noble character (akhlakul karimah) in students through the Habit Character Life Skill program and the Teacher Habit program. - Nandar, Ade; Abdurrahman; Asep Dudi (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2025)
This study discusses the implementation of the Habit Character Life Skill (HCL) program and the Habit Guru program in the development of akhlakul karimah (noble character) in students at MI Cerdas Nurani. The main objective of this research is to analyze the design of organization, implementation, monitoring, and evaluation of the HCL and Habit Guru programs in shaping students' character. The method used in this research is a qualitative approach with data collection techniques through semi-structured interviews, observations, and documentation studies. Data were obtained from informants consisting of the school principal, program managers, class teachers, and parents of the students. The findings indicate that the HCL and Habit Guru programs are effective in improving students' moral behavior, with significant changes in their moral and ethical conduct. These programs not only instill good habits but also strengthen the relationship between students, teachers, and parents in fostering akhlakul karimah. Furthermore, this study identifies indicators of students' behavioral changes as a direct impact of these programs, which include changes in daily habits as well as more positive mindsets and actions. These findings are expected to contribute to the development of character education in Islamic education, particularly in the implementation of programs that involve all elements of the school.